A Multicenter Study on Amidolytic Factor X Evaluation in Oral Anticoagulant Therapy - Berthier, A M; Pommereuil, M; Scarabin, P Y; Conard, J (Thrombosis and Haemostasis, 1985)
For laboratory control of oral anticoagulation, amidolytic factor X (F X) determination may offer an alternative to standardization difficulties of prothrombin time (PT). In order to validate this amidolytic assay on a large scale, a multicenter study was undertaken in 6 French laboratories using the same chromogenic substrate (Stachrom X Stago) and different automated instruments. Intra and between laboratory reproducibility of factor X was estimated on fresh and lyophilized patients plasmas and was found to be highly satisfactory. Standardization of the method did not seem to depend on the chromogenic substrate used, as investigated in two different centers. Results of PT and factor X were compared in over 500 patients on a longterm stabilized oral anticoagulant treatment: there was a strong positive correlation between the 2 tests in each center. The therapeutic range for factor X was evaluated from therapeutic PT values reported by Duckert and Marbet for the different thromboplastin reagents: the estimated mean range was 21 to 32%.Pooling the results of the six different centers a concordant information for prothrombin time and factor X amidolytic assay was found in 76% of patients and a fully discordant response was present in 0.6%. The results suggest that amidolytic factor X may be suitable for monitoring long-term anticoagulation. However, prospective trials are needed to evaluate its usefulness as compared to conventional methods.
Keywords: Oral anticoagulation; Chromogenic substrate; Amidolytic factor X; Prothrombin time